Organic-inorganic interpenetrating network surface protection material as well as preparation method and application method thereof

By applying organic and inorganic interpenetrating network surface protection materials on the surface of light alloys, engineering plastics and other materials, the problem of insufficient wear resistance of materials in the prior art is solved, and the comprehensive performance of high surface hardness, low dynamic friction coefficient, and high temperature resistance is improved.

CN119613989APending Publication Date: 2025-03-14LIAONING SILICATE RES INST
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411859006.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to provide a surface protection material that can not only improve the surface wear resistance of light alloys, engineering plastics and other materials, but also has comprehensive properties such as high hardness, low dynamic friction coefficient, and high temperature resistance.

Method used

The organic and inorganic interpenetrating network surface protection material is used. This material is widely dispersed and evenly mixed components such as wear-resistant particles, oxide particles, fibers and other components in a closed container with cooling function, and mixed with curing additives, inorganic acids and other components to form a crosslinked structure, and fully penetrated with organic components to form an organic and inorganic interpenetrating network.

Benefits of technology

It achieves the comprehensive performance of surface protection materials such as good wear resistance, high hardness, low dynamic friction coefficient, and high temperature resistance, and is suitable for a variety of surface protection applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613989A_ABST
    Figure CN119613989A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of protective materials, in particular to an organic-inorganic interpenetrating network surface protective material which comprises the following components in percentage by mass: 1-20% of wear-resistant particles; 100 to 150 parts of oxide particles; 1-15 parts of a curing aid; 5-20 parts of fiber; 1-15 parts of inorganic acid; 50 to 300 parts of solvent; and 1-7 parts of an auxiliary agent. The invention discloses an organic-inorganic interpenetrating network surface protection material and a preparation and application method thereof, and mainly aims to form a functional protection material with excellent wear resistance, high hardness, low friction force, high temperature resistance and good binding force and toughness for various surfaces.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of protective materials, and in particular to an organic-inorganic interpenetrating network surface protective material and a preparation method and an application method thereof. Background Art

[0002] Organic-inorganic interpenetrating network is a material that forms a cross-linked network structure including organic and inorganic inside a material, and the two can be fully combined to form a special composite system. Traditional organic interpenetrating network generally refers to a molding method of a material that brings a series of new properties including mechanical properties to the material through physical entanglement and entanglement between polymer chains. The organic-inorganic interpenetrating network disclosed in the present invention utilizes the interaction between two materials with completely different properties. Compared with the two traditional material molding methods of adding inorganic additives to organic materials and adding organic additives to inorganic materials, it can better balance the proportion of the two components and product performance, and can effectively improve the material construction molding process performance.

[0003] The existing organic-inorganic coexistence system is widely used and the technology is mature. Among them, the most common application form is to add inorganic additives to the organic continuous phase. In the final product, the inorganic additives are often dispersed in the organic phase in an independent form, and there is little or no interaction between the dispersed inorganic particles. Inorganic fiber-reinforced organic resin composites are an exception. Inorganic materials naturally form a continuous phase and are compounded with the organic continuous phase, giving the composites unique properties that the dispersed inorganic additives do not have. However, the complex preparation process of fiber-reinforced composites limits their application areas. For example, it is difficult to use continuous fiber-reinforced composites as surface protection materials.

[0004] With the increasing demand for wear resistance of material surfaces in the mining, chemical, aviation, aerospace and military fields, especially for light alloys, engineering plastics and other materials that are not wear-resistant in the traditional sense but have excellent mechanical and corrosion resistance properties and low overall cost, there is an obvious demand for additional surface protection materials. At present, there is no mature solution in the market.

[0005] The present invention discloses an organic-inorganic interpenetrating network surface protection material and an application process of the surface protection material. The surface protection material formed by the present invention has good wear resistance, high hardness, low dynamic friction coefficient, high temperature resistance and other good effects, and has excellent comprehensive performance.

[0006] The materials such as insulating coating disclosed in Chinese patents CN112778861A, CN112011250A, CN102433055B, etc. are mainly composed of water-soluble phosphoric acid or other inorganic acid salts, combined with water-based organic resins and other fillers, and are mostly used for insulation treatment of metal surfaces such as electrical steel. At the same time, in order to improve operating efficiency, the high-temperature curing time is generally short. This technology is mainly based on improving the surface insulation performance of the metal substrate. At the same time, the water-based organic resin is actually dispersed in the coating system in a granular form, and there is no substantial mutual reaction, and it is impossible to form effective cross-linking of organic components. Therefore, according to the disclosed patent technology, this type of insulating coating material mostly relies on the reaction between the coating and the surface of the electrical steel to work, which is essentially a special metal surface acid passivation anti-corrosion process.

[0007] The material technologies disclosed in Chinese patents CN110903738B, CN110885583B, CN109111824A, CN108249880A, CN109233564A, CN106467653B, etc., use inorganic acids, inorganic acid salts, inorganic acid polymers, etc. as functional fillers to play the role of flame retardancy, corrosion resistance, flash rust prevention or insulation, etc. Among them, the inorganic components used as fillers in the disclosed technical means are usually low in content. It can be seen from the composition, preparation and curing process disclosed in the patent that an effective inorganic cross-linking system cannot be formed in the material.

[0008] In the material technologies disclosed in Chinese patents CN103287568B, CN103395194A, etc., materials such as "phosphate adhesives" or "phosphate-based coatings" are used as internal bonding or interface materials in the composite material molding process to provide bonding to inorganic fibers, or to make the composite launch tube have the effects of corrosion resistance and resistance to high-speed flame erosion. However, as one of the materials used in the disclosed technology, it is not clearly described and limited as part of the invention. In addition, the inventors found in production and application that the use of phosphates as adhesives or coatings has a significant impact on the viscosity and construction process of the coating itself, and the hardness and wear resistance of the final product will also deteriorate.

[0009] There are no reports on a surface protection material that uses an organic-inorganic interpenetrating network that is solidified on the surface of a protected substrate, as well as a process and application technology for forming the surface protection material. Summary of the invention

[0010] The present invention discloses an organic-inorganic interpenetrating network surface protection material and an application process of the surface protection material. The surface protection material formed by the present invention has good wear resistance, high hardness, low dynamic friction coefficient, high temperature resistance and other good effects, and has excellent comprehensive performance; the mass ratio of each component is as follows:

[0011]

[0012] Furthermore, the wear-resistant particles are granulated powders with a Mohs hardness ≥ 6, such as zinc oxide, silicon dioxide, zirconium oxide, aluminum oxide, magnesium oxide, silicon carbide, boron carbide, tungsten carbide, boron nitride, glass powder, magnesium aluminum spinel, and molybdenum disulfide, graphite, calcium phosphate, calcium hydroxide, zinc pyrophosphate, zinc sulfide, zinc oxide, calcium fluoride, polytetrafluoroethylene, and polyethylene, or a mixture of several of them.

[0013] Furthermore, the wear-resistant particles are spherical particles with a particle size of 0.05 to 500 microns, or a mixture of particles with a particle size of 0.05 to 500 microns.

[0014] Furthermore, the wear-resistant particles preferably have a particle size of 0.1 to 100 microns.

[0015] Furthermore, the wear-resistant particles are preferably spherical particles formed by physical or chemical methods such as plasma spheroidization or sol-gel method.

[0016] Furthermore, the wear-resistant particles are preferably used in an amount of 3 to 15.

[0017] Furthermore, the oxide particles are one or a mixture of all or part of the oxides of calcium, zirconium, titanium, manganese, chromium, magnesium, zinc, aluminum, barium, copper, molybdenum, and silicon.

[0018] Furthermore, the oxide particles have a particle size of 0.2 to 500 microns, or a mixture of particles having a particle size of 0.2 to 500 microns.

[0019] Furthermore, the particle size of the oxide particles is preferably 0.5 to 100 microns.

[0020] Furthermore, the surface of the oxide particles is preferably physically modified by high temperature sintering.

[0021] Furthermore, the oxide particles are preferably sintered at 500-1500° C. for physical surface modification.

[0022] Furthermore, the surface of the oxide particles is preferably modified using an aqueous boric acid solution.

[0023] Furthermore, the oxide particles are preferably surface modified by using a boric acid aqueous solution with a mass concentration of 0.5 to 15%, soaking for 1 to 10 hours, and then drying at 150 to 450°C.

[0024] Furthermore, the oxide particles are preferably surface-modified using a boric acid aqueous solution with a pH of 1 to 6.

[0025] Furthermore, the oxide particles are preferably surface-modified by immersion in a boric acid aqueous solution at a temperature of 30 to 90°C.

[0026] Furthermore, the preferred amount of oxide particles is 120-140.

[0027] Furthermore, the curing aid is one or a mixture of chromium trioxide, chromium trioxide, aluminum nitride, aluminum hydroxide, aluminum hydroxide sol, magnesium oxide, magnesium hydroxide, cupric oxide, cuprous oxide, ferric oxide, ferrous oxide, ferrosoferric oxide, zirconium oxide, ammonium borate, ammonium chloride, aluminum chloride, ferric chloride, cupric chloride, aluminum fluoride, aluminum nitride, iron nitride, and silicon nitride.

[0028] Furthermore, the particle size of the curing aid is 0.05 to 0.1 micrometer, or a mixture of 0.05 to 0.1 micrometer.

[0029] Furthermore, the curing agent is a hydrosol with a particle size of 0.05 to 0.1 micrometer, or a mixture of hydrosols with a particle size of 0.05 to 0.1 micrometer.

[0030] Furthermore, the curing aid is an acidic aqueous solution mixture.

[0031] Furthermore, the curing aid is a dissolution product of the curing aid in water with a pH of 1 to 3, and the pH of the aqueous solution is adjusted using phosphoric acid, hydrochloric acid, sulfuric acid or nitric acid.

[0032] Furthermore, the pH of the aqueous curing agent solution is preferably adjusted using phosphoric acid or hydrochloric acid.

[0033] Furthermore, the preferred amount of the curing aid is 5 to 8.

[0034] Furthermore, the fiber is one or a mixture of carbon fiber, polymer fiber, glass fiber, high silica fiber, ceramic fiber, basalt fiber, and whiskers formed by oxides, carbides, sulfates, and silicates.

[0035] Furthermore, the fibers are chopped fibers or fiber powder.

[0036] Furthermore, the length of the fiber is 0.1 to 10 mm.

[0037] Furthermore, the aspect ratio of the fiber is greater than or equal to 10.

[0038] Furthermore, the fiber is preferably a mixture of carbon fiber, glass fiber and high silica fiber.

[0039] Furthermore, the fiber length is preferably 0.5 to 0.8 mm.

[0040] Furthermore, the fiber diameter is preferably less than or equal to 0.05 mm.

[0041] Furthermore, the fibers are preferably subjected to physical surface modification by high temperature sintering.

[0042] Furthermore, the fiber is preferably sintered in an air atmosphere at 400-700° C. to undergo physical surface modification.

[0043] Furthermore, the time for high-temperature sintering of the fiber for physical surface modification is 2 to 6 hours.

[0044] Furthermore, the fibers can preferably be wet-milled to obtain the desired size.

[0045] Furthermore, the fiber dosage is preferably 10 to 15.

[0046] Furthermore, the inorganic acid is one or a mixture of phosphoric acid, hydrochloric acid, nitric acid and sulfuric acid.

[0047] Furthermore, the inorganic acid is preferably a mixture of phosphoric acid, hydrochloric acid and sulfuric acid.

[0048] Furthermore, the inorganic acid is preferably concentrated phosphoric acid: concentrated hydrochloric acid: concentrated sulfuric acid in a mass ratio of 1-1.3: 0.2-0.5: 0.5-0.8.

[0049] Furthermore, the inorganic acid is preferably a diluted acid aqueous solution.

[0050] Furthermore, the inorganic acid aqueous solution preferably has a mass concentration of 5 to 30%, or a pH value less than or equal to 2.

[0051] Furthermore, the inorganic acid is preferably a solution of a mixture of water and alcohol.

[0052] Furthermore, the inorganic acid water and alcohol mixture solution preferably has a mass ratio concentration of 3 to 25%, or a pH value less than or equal to 2.

[0053] Furthermore, the solvent is one or a mixture of water, methanol, ethanol, propanol, isopropanol, glycerol, ethylene glycol, formic acid, acetic acid, and citric acid.

[0054] Furthermore, the TDS of water in the solvent is preferably less than or equal to 200 ppm.

[0055] Furthermore, the solvent is preferably a mixture of water, ethanol and citric acid.

[0056] Furthermore, the solvent preferably used is water:ethanol:citric acid in a mass ratio of 100-130:10-30:1-5.

[0057] Furthermore, the inorganic acid is preferably used in an amount of 4 to 8.

[0058] Furthermore, the auxiliary agent is one or more of a defoamer, a surface energy modifier, and a structure control agent. The defoamer is a defoamer commonly used in industry. The present invention preferably uses a modified silicone defoamer. The surface energy modifier is a surface energy modifier commonly used in industry. The present invention preferably uses a mixture of nonionic and cationic surface energy modifiers. The structure control agent is an inorganic or organic structure control agent commonly used in industry. The present invention preferably uses white carbon black as a structure control auxiliary agent.

[0059] Furthermore, the structure control agent is preferably white carbon black with a hydrophobic surface treatment.

[0060] Furthermore, the structure control agent preferably has a specific surface area greater than or equal to 100 m 2 / g of white carbon black.

[0061] Furthermore, the mass ratio of the auxiliary agent mixture is as follows:

[0062] Defoaming agent 2-5;

[0063] Surface energy modifier 0~3;

[0064] Structure control agent 0~5.

[0065] Furthermore, the preferred mass ratio of the auxiliary agent mixture is as follows:

[0066] Defoamer 2.5~3.5;

[0067] Surface energy modifier 1.5~2.5;

[0068] Structure control agent 3~4.

[0069] According to another aspect of the present invention, a method for preparing an organic-inorganic interpenetrating network surface protection material is provided, which is carried out according to the following steps:

[0070] (1) Dispersing the wear-resistant particles, oxide particles, fibers, part of the additives, and part of the solvent in a closed container with a cooling function at a high speed of 1500 to 3000 rpm for 30 to 60 minutes; uniformly mixing, filtering through a 50 to 500 mesh filter, and then filling and sealing to obtain component A;

[0071] (2) Dispersing the curing aid, inorganic acid, remaining solvent and remaining additives in another container at a high speed of 500 to 1500 rpm, controlling the dispersion temperature at 30 to 90° C. for 10 to 30 minutes; after complete cooling, standing for 5 to 30 minutes, uniformly mixing, and filling and sealing in a sealed container with a temperature control function, which is component B;

[0072] (3) Component A and component B are mixed to obtain a surface protection material.

[0073] The present invention also provides an application method of an organic-inorganic interpenetrating network surface protection material, comprising the following steps:

[0074] (1) After cleaning the surface of the protective substrate 1, a sacrificial material 2 and a surface protective material 3 are sequentially applied; wherein the sacrificial material 2 is one or a mixture of LQK-CC-987 (Liaoning Light Industry Science Research Institute Co., Ltd.), a silicone oil solution, and an aqueous dispersion of silicone oil; the silicone oil emulsion of the sacrificial material 2 is a solution of polymethylsiloxane with a viscosity of 50 to 5000 mPa·s and an alkane mass ratio of 5 to 30%; the film thickness of the sacrificial material 2 is 20 to 500 μm, and the drying time of the sacrificial material 2 after application is 5 minutes to 2 hours; the surface protective material 3 is prepared by mixing component A and component B; and the thickness is 10 to 1000 μm;

[0075] (2) curing the surface protection material 3; the surface protection material 3 is cured at room temperature for 1 to 7 days; the curing temperature is 180 to 200° C., and the curing time can be 2 to 6 hours;

[0076] (3) Applying an organic component 4 on the surface of the surface protection material 3; the organic component 4 fully penetrates the surface and the interior of the surface protection material 3; wherein the organic component 4 is a thermoplastic or thermosetting organic material such as epoxy resin, phenolic resin, acrylic resin, silicone resin, silicone rubber, rubber, or a mixture of one or more of the above organic materials after reinforcement; the application thickness of the organic component 4 is 100 to 2000 microns; the viscosity of the organic component 4 is 50 to 10000 mPa·s; the penetration time of the organic component 4 into the cured surface protection material 3 is 5 to 20 minutes;

[0077] (4) constructing a protective substrate 5 on the surface of the organic component 4;

[0078] (5) curing the organic component 4;

[0079] (6) The surface protection material 3, the organic component 4 and the protective substrate 5 are separated from the surface of the sacrificial material 2 by external force, deformation, vibration, temperature or chemical methods, or by self-separation during the material forming stage, to obtain a material protected by the organic-inorganic interpenetrating network surface protection material.

[0080] The present invention discloses an organic-inorganic interpenetrating network surface protection material and its preparation and application method, the main purpose of which is to form a functional protection material for various surfaces with excellent wear resistance, high hardness, low friction, high temperature resistance, and good bonding strength and toughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0081] Figure 1 is a schematic diagram of an application method of the protective material of the present invention;

[0082] Figure 2 Implementation example and commercially available inorganic wear-resistant coating material after test 1. DETAILED DESCRIPTION

[0083] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0084] The material obtained by curing component A and component B disclosed in the present invention is mainly an inorganic component and can form a cross-linked structure. Through full penetration and combination with the organic component during the construction process, the formed organic-inorganic interpenetrating network has unique properties that the inorganic and organic materials do not have when they exist alone. Compared with a single continuous phase material formed by adding inorganic materials to organic materials or adding organic materials to inorganic materials, this organic-inorganic interpenetrating network effectively balances the proportions of the two components while taking into account the cross-linking characteristics of the two substances, and better reduces the difficulty of material construction.

[0085] By using a molded substrate and a sacrificial material, it is possible to ensure that the organic-inorganic interpenetrating network surface protection material disclosed in the present invention can provide good protection for the surfaces of various different protected materials. Combined with the good bonding force formed between the organic component and the surface of the protected material, the organic-inorganic interpenetrating network surface protection material can be applied to the surfaces of various materials that have been formed or not fully formed, including metals, resins, rubber and plastics, ceramics, glass, films, etc. At the same time, according to specific usage requirements, users can also flexibly design the thickness of the protection material according to the different external conditions of the surface of the protected material.

[0086] The organic-inorganic interpenetrating network surface protection material disclosed in the following application examples is used to protect the surface of pure copper plates (thickness 0.5 mm), basalt continuous fiber silicone resin-based composite materials (thickness 2 mm), and glass fiber cloth wrapped reinforced HDPE slices (thickness 3 mm). After the construction is completed, the organic-inorganic interpenetrating network surface protection material is tested in two ways using a reciprocating friction tester (Ruijin Instruments), and compared with a commercially available high-hardness inorganic wear-resistant coating (substrate aluminum alloy thickness 2 mm, coating thickness 100 microns, curing temperature 220°C). Test method 1 parameters are friction block contact area 2cm 2 , load 1kg, friction contact surface is aluminum alloy, cycle speed is 60 times / min, number of cycles is 500 times, friction track length is 10cm; test method 2 parameters are friction block contact area 2.25cm 2, load 2.5kg, friction contact is 60 mesh silicon carbide water sandpaper, cycle speed is 30 times / minute, number of cycles is 300 times, and the friction track length is 10cm. After each of the above tests, the friction contact medium is replaced. The test records the mass change of the test piece before and after the friction test, and observes the surface of the test piece after the friction test. The exposure of the protected material is defined as material failure. The test results are shown in Table 1. The status of some test pieces after the test is as follows Figure 2 As shown, (from left to right: Implementation Examples 1 to 3, commercially available inorganic wear-resistant coating).

[0087] Table 1 Friction test results of implementation examples 1 to 3 and a commercially available inorganic wear-resistant coating material

[0088]

[0089] *+,- refer to the increase and decrease of mass

[0090] The above test method is closer to the actual use conditions of certain materials that require surface protection, and can quickly and effectively screen surface protection materials. The test phenomena and test results in Table 1 show that compared with some commercially available inorganic wear-resistant coatings, the organic-inorganic interpenetrating network surface protection material disclosed in the present invention has better wear resistance and protection effects. At the same time, due to the characteristics of material composition and construction technology, the formed organic-inorganic interpenetrating network can effectively improve the apparent state of the protective material, and largely avoid defects such as orange peel and sagging that are prone to occur in traditional coating materials.

[0091] Implementation Example 1

[0092] A preparation method and application mode of an organic-inorganic interpenetrating network surface protection material. 1 kg of spherical silicon dioxide particles (200 μm, Liaoning Wuke New Material Industry Research Co., Ltd.), 4 kg of spherical alumina (100 μm, Liaoning Wuke New Material Industry Research Co., Ltd.), 0.5 kg of graphite powder (300 mesh, 90%, Chenzhou Jili), 35 kg of magnesium oxide (300 μm, Shanghai MCC, sintered at 1000°C for 6 h), 85 kg of silicon dioxide (0.5 μm, Shanghai MCC, sintered at 600°C for 6 h), 8 kg of high-silica fiber powder (length 0.5-1 mm, wet ball milling, Liaoning Light Industry Science Research Institute Co., Ltd.), 2 kg of carbon fiber powder (length 0.2-0.5 mm, Japan Toray), 80 kg of pure water (TDS≤50 ppm, homemade by distillation), 2 kg of BYK-028 (BYK), and 1 kg of WET KL 245 (TEGO) were put into a high-speed disperser for sealed high-speed dispersion. The dispersion process is 1500rpm for 10 minutes, 2000rpm for 10 minutes, and 3000rpm for 20 minutes. After filtering through 300 mesh, it is filled as component A for standby use.

[0093] In another high-speed disperser, 1 kg of aluminum nitride (0.2 μm, Shanghai MCC), 1.5 kg of ferroferric oxide (Sinopharm, AR), and 2.5 kg of pure water were added, and the pH was adjusted to 1.0 with concentrated hydrochloric acid. The mixture was heated to 50°C at 500 rpm and dispersed for 10 minutes. Then, 50 kg of pure water, 5 kg of concentrated phosphoric acid (Sinopharm, AR), 3 kg of concentrated hydrochloric acid (Sinopharm, AR), 2 kg of concentrated sulfuric acid (Sinopharm, AR), 1.3 kg of BYK-028, and 0.7 kg of WET KL 245 were added, and the mixture was heated to 80°C for high-speed dispersion. After the dispersion process was 1500 rpm for 15 minutes, the dispersion speed was reduced to 500 rpm and the mixture was dispersed for another 10 minutes. The mixture was cooled to room temperature and allowed to stand for 20 minutes. The component B was then filled and prepared for use.

[0094] After the surface of the stainless steel plate was degreased and cleaned, a 50-micron thick LQK-CC-987 was applied to the surface by scraping with a scraper. After drying for 10 minutes, a surface protection material was applied after evenly mixing component A and component B. The construction thickness was 100 microns. After curing at room temperature for 3 days, a 250-micron thick epoxy resin (Easy Composite) with a viscosity of 2000mPa·s and a curing agent was infiltrated into the surface protection material by brushing. After 15 minutes, a 0.5mm thick copper plate was covered on the surface of the uncured epoxy resin and cured at 40℃~100℃ for 120 minutes. After the curing was completed and cooled to room temperature, the copper plate covered with the surface protection material was separated by shear force to obtain the final product. Some wear resistance test results are shown in Table 1. The surface of the sample did not change after being heated by a 1200℃ propane flame for 50 minutes. After cooling, the wear test was carried out, and there was no obvious loss in wear resistance.

[0095] Implementation Example 2

[0096] A preparation method and application mode of an organic-inorganic interpenetrating network surface protection material. 8 kg of alumina spherical particles (50 μm, Liaoning Wuke New Materials Industry Research Co., Ltd.), 1 kg of zirconium oxide spherical particles (0.1 μm, Liaoning Wuke New Materials Industry Research Co., Ltd.), 1 kg of calcium hydroxide (100 μm, homemade), 85 kg of titanium dioxide (50 μm, Shanghai MCC, sintered at 1000°C for 6 h), 35 kg of alumina (200 nm, Shanghai MCC, washed with 5% boric acid and soaked for 5 h and dried), 10 kg of silicon dioxide (200 μm, Shanghai MCC, dried), 3 kg of high silica fiber powder (length 0.5-1 mm, wet ball milling, Liaoning Light Industry Science Research Institute Co., Ltd.), 2 kg of borosilicate glass fiber powder (length 0.5-1.3 mm, wet ball milling, homemade), 150 kg of pure water (TDS ≤ 50 ppm, homemade by distillation), 0.35 kg of FORMEX 810 (TEGO), WET 0.25 kg of TEGO 270 and 0.3 kg of AEROSIL 200 (EVONIK) were placed in a high-speed disperser for sealed high-speed dispersion. The dispersion process was 1500 rpm for 20 minutes and 3000 rpm for 20 minutes. After filtering through 400 mesh, it was filled as component A for standby use.

[0097] In another high-speed disperser, 0.35 kg of magnesium hydroxide (Sinopharm, AR), 1.35 kg of silicon nitride (Sinopharm, AR), 0.1 kg of ammonium chloride (Sinopharm, AR), and 0.2 kg of purified water were added, and the pH was adjusted to 1.0 with concentrated hydrochloric acid. The mixture was heated to 40°C at 500 rpm and dispersed for 10 minutes. Then, 100 kg of purified water, 3 kg of concentrated hydrochloric acid (Sinopharm, AR), 2 kg of concentrated sulfuric acid (Sinopharm, AR), 0.17 kg of FORMEX 810, 0.13 kg of WET 270, and 0.15 kg of AEROSIL 200 were added, and the mixture was heated to 90°C for high-speed dispersion. The dispersion process was 1500 rpm for 30 minutes, and then the mixture was cooled to room temperature and allowed to stand for 20 minutes. Component B was filled and prepared for use.

[0098] After the surface of the stainless steel plate was degreased and cleaned, a 20-micron thick polydimethylsiloxane 30% mass ratio petroleum ether solution was applied to the surface by dip coating. After drying for 30 minutes, the surface protection material after the uniform mixture of component A and component B was dip coated, and the construction thickness was 150 microns. Curing at 200℃ for 6h. A 500-micron thick silicone resin (MSE100, WACKER) with a viscosity of about 1000mPa·s was infiltrated into the surface protection material by spraying. After standing for 15 minutes, the basalt continuous fiber silicone resin prepreg (resin is MSE100, 15 layers, homemade) was covered on the surface of the uncured resin, and cured in an autoclave at 40℃~150℃ for 3 hours. After the curing was completed and cooled to room temperature, the basalt fiber material covered with the surface protection material was separated from the stainless steel plate by vibration using a leather hammer to obtain the final product. Some wear resistance test results are shown in Table 1.

[0099] Implementation Example 3

[0100] A preparation method and application mode of an organic-inorganic interpenetrating network surface protection material. 1 kg of zinc oxide spherical particles (100 μm, Liaoning Wuke New Materials Industry Research Co., Ltd.), 1 kg of zirconium oxide spherical particles (0.1 μm, Liaoning Wuke New Materials Industry Research Co., Ltd.), 4 kg of silicon carbide (200 μm, Shanghai MCC), 60 kg of silicon dioxide (200 μm, Shanghai MCC) that was previously impregnated with 10% boric acid aqueous solution and then sintered and dried, 20 kg of aluminum oxide (200 nanometers, Shanghai MCC) and 20 kg of magnesium oxide (100 μm, Shanghai MCC) were also added to the tank, and then 10 kg of Kevlar fiber powder (length 0.1-1 mm, DuPont), 5 kg of basalt fiber powder (length 0.8-1.0 mm, wet ball milling, Liaoning Qingke Composite Materials Technology Co., Ltd.), 150 kg of pure water (TDS ≤ 50 ppm, homemade by distillation), 30 kg of ethanol (National Pharmaceutical Group, AR), 1 kg of citric acid monohydrate (National Pharmaceutical Group, AR), AIREX 0.5 kg of 902W (TEGO) and 0.5 kg of AEROSIL 300 (EVONIK) were placed in a high-speed disperser for sealed high-speed dispersion. The dispersion process was 1500 rpm for 10 minutes and 3000 rpm for 50 minutes. After filtering through 50 mesh, it was filled as component A for standby use.

[0101] In another high-speed disperser, add 2 kg of aluminum hydroxide sol powder (200 μm, 100% solid content), 1 kg of aluminum fluoride (Sinopharm, AR), 0.1 kg of ferric chloride (Sinopharm, AR), and 0.5 kg of purified water. After adjusting the pH to 1.0 with concentrated hydrochloric acid, heat to 40°C at 500 rpm and disperse for 20 minutes. Then add 100 kg of purified water, 20 kg of ethanol, 0.6 kg of citric acid monohydrate, 1 kg of concentrated sulfuric acid (Sinopharm, AR), 1 kg of concentrated phosphoric acid (Sinopharm, AR), 1 kg of AIREX 902W, and 0.5 kg of AEROSIL300, heat to 80°C for high-speed dispersion, and the dispersion process is 1500 rpm for 30 minutes. After cooling to room temperature and standing for 30 minutes, fill and obtain component B for standby use.

[0102] After the surface of the stainless steel plate is degreased and cleaned, a 20-micron thick LQK-CC-987 is applied to the surface by brushing. After drying for 1 hour, the surface protection material after component A and component B are evenly mixed is applied by brushing, and the construction thickness is 100 microns. Curing at 200℃ for 6h. A 250-micron thick epoxy-modified silicone resin with a viscosity of about 1000mPa·s and a curing agent (Hubei Longsheng Sihai, heat preservation to 80℃ during construction) is infiltrated into the surface protection material by brushing. After standing for 15 minutes, HDPE slices (glass fiber reinforced) are covered on the surface of the uncured resin, and pressurized and cured at 40℃~120℃ for 5 hours. After the curing is completed and cooled to room temperature, the material detaches from the stainless steel plate by itself to obtain the final product. Some wear resistance test results are shown in Table 1.

[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An organic-inorganic interpenetrating network surface protection material, characterized in that: The mass ratio of each component is as follows:

2. The organic-inorganic interpenetrating network surface protection material according to claim 1, characterized in that: The wear-resistant particles are granulated powders with a Mohs hardness of ≥6, such as zinc oxide, silicon dioxide, zirconium oxide, aluminum oxide, magnesium oxide, silicon carbide, boron carbide, tungsten carbide, boron nitride, glass powder, magnesium aluminum spinel, and molybdenum disulfide, graphite, calcium phosphate, calcium hydroxide, octyl pyrophosphate, zinc sulfide, zinc oxide, calcium fluoride, polytetrafluoroethylene, and polyethylene, or a mixture of several of them.

3. An organic-inorganic interpenetrating network surface protection material as claimed in claim 1, characterized in that: The oxide particles are one or a mixture of all or part of the oxides of calcium, zirconium, titanium, manganese, chromium, magnesium, zinc, aluminum, barium, copper, molybdenum and silicon.

4. The organic-inorganic interpenetrating network surface protection material according to claim 1, characterized in that: The curing aid is one or a mixture of chromium trioxide, chromium trioxide, aluminum nitride, aluminum hydroxide, aluminum hydroxide sol, magnesium oxide, magnesium hydroxide, cupric oxide, cuprous oxide, ferric oxide, ferrous oxide, ferroferric oxide, zirconium oxide, ammonium borate, ammonium chloride, aluminum chloride, ferric chloride, cupric chloride, aluminum fluoride, aluminum nitride, iron nitride, and silicon nitride.

5. The organic-inorganic interpenetrating network surface protection material according to claim 1, characterized in that: The fiber is one or a mixture of carbon fiber, polymer fiber, glass fiber, high silica fiber, ceramic fiber, basalt fiber, and whiskers formed by oxides, carbides, sulfates, and silicates.

6. The organic-inorganic interpenetrating network surface protection material according to claim 1, characterized in that: The inorganic acid is one or a mixture of phosphoric acid, hydrochloric acid, nitric acid and sulfuric acid; it is a diluted acid aqueous solution; the mass ratio concentration of the inorganic acid aqueous solution is 5-30%, or the pH is less than or equal to 2.

7. The organic-inorganic interpenetrating network surface protection material according to claim 1, characterized in that: The solvent is one or a mixture of water, methanol, ethanol, propanol, isopropanol, glycerol, ethylene glycol, formic acid, acetic acid, and citric acid.

8. The organic-inorganic interpenetrating network surface protection material according to claim 1, characterized in that: The auxiliary agent is one or more of a defoamer, a surface energy modifier, and a structure control agent; the defoamer is a commonly used defoamer in industry; the surface energy modifier is a commonly used surface energy modifier in industry; and the structure control agent is an inorganic or organic structure control agent commonly used in industry.

9. A method for preparing an organic-inorganic interpenetrating network surface protection material, characterized in that: The following steps are included: (1) Dispersing the wear-resistant particles, oxide particles, fibers, part of the additives, and part of the solvent in a closed container with a cooling function at a high speed of 1500 to 3000 rpm for 30 to 60 minutes; uniformly mixing, filtering through a 50 to 500 mesh filter, and then filling and sealing to obtain component A; (2) Dispersing the curing aid, inorganic acid, remaining solvent and remaining additives in another container at a high speed of 500 to 1500 rpm, controlling the dispersion temperature at 30 to 90° C. for 10 to 30 minutes; after complete cooling, standing for 5 to 30 minutes, uniformly mixing, and filling and sealing in a sealed container with a temperature control function, which is component B; (3) Component A and component B are mixed to obtain a surface protection material.

10. An application method of an organic-inorganic interpenetrating network surface protection material, characterized in that: The following steps are included: (1) After cleaning the surface of the protective substrate 1, a sacrificial material 2 and a surface protective material 3 are sequentially applied; wherein the sacrificial material 2 is a mixture of one or more of LQK-CC-987, a silicone oil solution, and an aqueous dispersion of silicone oil; the silicone oil emulsion of the sacrificial material 2 is an alkane solution with a mass ratio of 5 to 30% of polymethylsiloxane with a viscosity of 50 to 5000 mPa·s; the film thickness of the sacrificial material 2 is 20 to 500 μm, and the drying time of the sacrificial material 2 after application is 5 minutes to 2 hours; the surface protective material 3 is prepared by mixing component A and component B; and the thickness is 10 to 1000 μm; (2) curing the surface protection material 3; the surface protection material 3 is cured at room temperature for 1 to 7 days; the curing temperature is 180 to 200° C., and the curing time can be 2 to 6 hours; (3) Applying an organic component 4 on the surface of the surface protection material 3; the organic component 4 fully penetrates the surface and the interior of the surface protection material 3; wherein the organic component 4 is a thermoplastic or thermosetting organic material such as epoxy resin, phenolic resin, acrylic resin, silicone resin, silicone rubber, rubber, or a mixture of one or more of the above organic materials after reinforcement; the application thickness of the organic component 4 is 100 to 2000 microns; the viscosity of the organic component 4 is 50 to 10000 mPa·s; the penetration time of the organic component 4 into the cured surface protection material 3 is 5 to 20 minutes; (4) constructing a protective substrate 5 on the surface of the organic component 4; (5) solidifying the organic component 4; (6) The surface protection material 3, the organic component 4 and the protective substrate 5 are separated from the surface of the sacrificial material 2 by external force, deformation, vibration, temperature or chemical methods, or by self-separation during the material forming stage, to obtain a material protected by the organic-inorganic interpenetrating network surface protection material.

Citation Information

Patent Citations

  • Chromium-free insulation coating material for non-oriented silicon steel

    CN102433055B

  • A large-area sandwich heat insulation structure for high-speed aircraft and its molding method

    CN103287568B

  • Manufacture method for composite-material launch canister of high-altitude fire-extinguishing rocket

    CN103395194A

  • Flame-retardant epoxy resin compositions, prepregs, insulating sheets, adhesive sheets, laminates, sealants, casting materials, and cured products.

    CN106467653B

  • Double-component surface repairing agent for bathtub as well as preparation method and using method of double-component surface repairing agent

    CN108249880A